2020
DOI: 10.1002/mds.28286
|View full text |Cite
|
Sign up to set email alerts
|

Dopa‐Responsive Parkinsonism in a Patient With Homozygous RFC1 Expansions

Abstract: We read the letter titled "RFC1 Intronic Repeat Expansions Absent in Pathologically Confirmed Multiple Systems Atrophy" published online in April 2020 1 with great interest. In light of that letter, we would like to expand the phenotypic spectrum of RFC1 expansion-related disorders by reporting dopa-responsive parkinsonism in a 63-year-old woman. She developed parkinsonian symptoms in her early 50s, characterized by bradykinesia, resting tremor, and stiffness. The patient was started on levodopa as a symptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…We found that the clinical phenotype of the three patients was consistent with PD and that their extrapyramidal symptoms unambiguously responded to levodopa. Patient 3 resembled a previous case of parkinsonism with biallelic RFC1 (AAGGG) exp in levodopa response, age of onset, dopamine transporter imaging and the presence of chronic cough 8 . However, the disease course appears to have been considerably milder in the previous patient, as her neuropathy was restricted to sensory fibers and, most importantly, she had ataxia 8 , which was not present in our patients.…”
mentioning
confidence: 56%
See 4 more Smart Citations
“…We found that the clinical phenotype of the three patients was consistent with PD and that their extrapyramidal symptoms unambiguously responded to levodopa. Patient 3 resembled a previous case of parkinsonism with biallelic RFC1 (AAGGG) exp in levodopa response, age of onset, dopamine transporter imaging and the presence of chronic cough 8 . However, the disease course appears to have been considerably milder in the previous patient, as her neuropathy was restricted to sensory fibers and, most importantly, she had ataxia 8 , which was not present in our patients.…”
mentioning
confidence: 56%
“…Patient 3 resembled a previous case of parkinsonism with biallelic RFC1 (AAGGG) exp in levodopa response, age of onset, dopamine transporter imaging and the presence of chronic cough 8 . However, the disease course appears to have been considerably milder in the previous patient, as her neuropathy was restricted to sensory fibers and, most importantly, she had ataxia 8 , which was not present in our patients. Another patient has been reported with levodopa-responsive lower body parkinsonism and with incomplete CANVAS 7 .…”
mentioning
confidence: 56%
See 3 more Smart Citations